Democratic competence and secondary school prefects’ interest in politics in Akure city (2024)
This research work is geared towards unravelling the composite factors as determinants of secondary school prefects’ interest in politics in Akure city. The researchers adopted descriptive survey research design. The multi-stage sampling procedure was used for this study. The balloting approach was used to select 20 schools from each of the two LGAs in Akure City, making a total of 40 schools. Simple random sampling technique was used to select 10 school prefects, making a total of 400 school prefects. However, only 390 students responded by filling the instruments appropriately. Structured questionnaires were used as instrument of data collection while mean and standard deviation and t-test statistical tools were used in analysing the data collected from the respondents. According to the findings of this study, there were significant differences in the means of school prefects’ interest in politics and each of democratic competence factors (Knowledge: t= -2.639; df: 389, P< (.009); Skills: t= 12.533; df: 389, P< (.000), Values: t= 58.005; df: 389, P< (.000); Attitude: t= 12.533, df: 389, P< (.000) at 0.05 level of significance. The implication of the findings of this research is that school prefects with adequate democratic knowledge, skills, values, and attitude tend to develop interest in politics. Therefore, the study recommended that the school prefects should be incorporated into the school decision making committee as the students are the major stakeholders in the education business, the school prefects should be exposed to democratic political activities both within and outside the school such as writing articles on political topics, attending political parties’ meeting etc. More importantly, schools should adopt secret ballot system in electing prefects by the generality of the students as this will make the prefects to be accountable to the students’ community not only to the school management alone.